Trains, bodies, landscapes. Experiencing distance in the long nineteenth century. Issue 2 (August 2019) - Geurts, Anna P. H.
The arrival of the railways has led scholars of nineteenth-century Europe to posit the thesis of a shrinking world, in which distances were annihilated and travel became a decorporealised and delocalised experience. This article uses travellers' own writings to empirically complicate this thesis by looking at which journeys were characterised as near or far, and why. Building on Massey's and Wenzlhuemer's work on the multiplicity of space and spatial power, the seemingly contradictory findings are explained by suggesting the coexistence of a number of different types of lived distance. The article thus offers a taxonomy of sorts, outlining those distance types that were experienced most often by western-European travellers – grounded in physical effort, landscape elements and other often highly specific, material characteristics of their journeys. Together, they suggest that distances remained a tangible reality to travellers, firmly anchored in their bodies and the physical spaces they occupied and traversed.